Strategi Perencanaan Gaji dan Insentif Finansial SDM Pendidikan Islam: Studi Pustaka pada Lembaga Pendidikan Islam - Yanova, Ekrita; Karim, Hamdi Abdul (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyse the concepts, principles, and strategies of salary and financial incentive planning for Islamic education HR based on a literature review. This study uses a library research method with a qualitative-descriptive approach, through analysis of books, scientific journals, and relevant academic sources in the fields of HR management, education, and Islamic education. The results of the study show that effective salary and incentive planning must be based on the principles of fairness, fairness, welfare, trust, and professionalism as taught in Islam. Strategies that can be implemented include setting competency- and performance-based salary standards, integrating financial and non-financial incentives, and ensuring managerial transparency and accountability. The main challenges include limited funding sources, weak internal policies, and resistance to system change. Therefore, managerial commitment and sustainable policies are needed so that salary and incentive planning can improve the overall quality of Islamic educational institutions.